Blood conservation strategies in cardiac valve replacement: A retrospective analysis of 1645 patients. Issue 41 (October 2016) - Zheng, Junnan; Chen, Liangwei; Qian, Linfeng; Jiang, Jianjie; Chen, Yinglian; Xie, Jue; Shi, Liping; Ni, Yiming; Zhao, Haige
Abstract : Abstract: We aimed to evaluate whether blood conservation strategies including intraoperative autologous donation (IAD) could reduce perioperative blood transfusion for patients undergoing cardiac valve replacement including mitral valve replacement, aortic valve replacement (AVR), and double valve replacement (DVR). A total of 726 patients were studied over a 3-year period (2011–2013) after the implementation of IAD and were compared with 919 patients during the previous 36-month period (January 2008–December 2010). The method of small-volume retrograde autologous priming, strict blood transfusion standard together with IAD constituted a progressive blood-saving strategy. Baseline characteristics and preoperative information showed no statistically significant difference between IAD group and non-IAD group. Most of the postoperative morbidities are statistically the same in the 2 groups. Chest tube output (415.2 vs 1029.8 mL, P  < 0.001) and postoperative respiratory failure (5.9% vs 8.6%, P = 0.039) favored the IAD group, whereas hematocrit levels were more favorable in the non-IAD group (30.3% vs 33.0% at the end of the operation, P  < 0.001; 30.4% vs 31.5% at the time of discharge). The use of blood product transfusion was higher in the non-IAD group (22.6% vs 43.3%, P  < 0.001). Binary multivariate logistic regression analysis showed that high age, non-IAD, DVR surgery, and absent smoking history are associated with a higher risk of intra-/postoperative blood transfusion. Blood conservation is effective and safe in cardiac valve replacement surgeries. The use of intraoperative autologous donation can lead to improved outcomes including a significantly lower rate of intra-/postoperative blood transfusion and postoperative complications.